2018
DOI: 10.1111/ecin.12753
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Housing Wealth Losses on Spending in the Great Recession

Abstract: We use panel data on a complete inventory of household spending and assets to estimate the spending response to the sharp and largely unexpected declines in house values that occurred in the Great Recession. Our study complements the existing literature on this topic by relying exclusively on longitudinal micro data on both household wealth and expenditure. Our data span the period 2002-2012, allowing us to separate trends in spending from innovations in response to unexpected wealth changes. We find the margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In addition to increasing financial complexity, there were dramatic shifts in housing prices and markets during the 1998 to 2014 period, with prices generally increasing substantially precrisis and falling precipitously after 2007. Importantly, there was also considerable variation in home price appreciation (and depreciation) across the country during our window of analysis, and prior research has documented sizeable responses of older households' expenditure (Angrisani, Hurd, and Rohwedder 2019), following heavy equity extraction during the boom and the drying up of this source of credit after the bust (Adelino et al 2016). To examine the dynamics between cognitive ability, changes in house values, and increasing financial complexity, we construct a one-year change measure in home values at a respondent's zip-code level and augment our primary specification with this measure.…”
Section: Cognitive Ability's Evolving Influence On Debt Burdensmentioning
confidence: 90%
“…In addition to increasing financial complexity, there were dramatic shifts in housing prices and markets during the 1998 to 2014 period, with prices generally increasing substantially precrisis and falling precipitously after 2007. Importantly, there was also considerable variation in home price appreciation (and depreciation) across the country during our window of analysis, and prior research has documented sizeable responses of older households' expenditure (Angrisani, Hurd, and Rohwedder 2019), following heavy equity extraction during the boom and the drying up of this source of credit after the bust (Adelino et al 2016). To examine the dynamics between cognitive ability, changes in house values, and increasing financial complexity, we construct a one-year change measure in home values at a respondent's zip-code level and augment our primary specification with this measure.…”
Section: Cognitive Ability's Evolving Influence On Debt Burdensmentioning
confidence: 90%
“…The interpretation of this result supports the hypothesis of the wealth effect because homeowners are more likely to benefit from increasing housing prices, particularly elderly homeowners who are likely to have higher home values. Angrisani et al (2019) found the marginal propensity to consume out of an unexpected housing wealth change to be 6 cents per dollar among older American households. As for homeowners, if housing prices do have an impact on consumption, then individuals should respond to increases in their housing wealth by either saving less or borrowing more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, from previous studies, in a region with high rates of homeownership and low loan interest rates, under the hypothesis of a housing wealth effect 3 , changes in housing prices should exert an influence on consumption expenditure, which will then further influence the performance of the economy. The reason is that housing by its sheltering nature generates personal expenditure 4 that directly and indirectly contributes towards the categories of consumption (Aladangady, 2017;Angrisani et al, 2019;Attanasio et al, 2009;Campbell & Cocco, 2007;Carrol et al, 2011;Case et al, 2005;Chen et al, 2010Chen et al, , 2018Cooper & Dynan, 2016;Dvornak & Kohler, 2007;Elbourne, 2008;Fereidouni & Tajaddini, 2017;Gan, 2010;Iacoviello & Neri, 2010;Muellbauer & Murphy, 2008;Paiella & Pistaferri, 2017;Simo-Kengne et al, 2013). As consumption is one of the main components in the formula for gross domestic product (GDP) 5 , it is considered that the impact of a housing wealth effect on consumption suggests that there exists a strong positive link between the housing market and macroeconomic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus even if only 10% was redistributed, the relative value would be similar to ARRA rebates. 6 Third, we are also interested in investigating whether the some of the sudden influx of deposits during this time was accompanied by subsequent increases in lending by the banking system, and thus possibly creating an expansionary effect in the medium term despite the decline in output in the short term. While all of these three factors suggest there might be an aggregate expansionary effect, in our research we focus on the regional effects where variations in the shocks are both more apparent, and the sample size lends itself to easier empirical analysis and causal inference.…”
Section: Introductionmentioning
confidence: 99%
“…According to a government sponsored but unreleased report in 2013 titled "Study on Unaccounted Incomes in India", the National Institute of Public Finance and Policy estimates that the shadow economy was about 45% of GDP(Table 4.16 ) for 2000-2010. The money to GDP ratio in the shadow economy is also certainly higher than 12% since the formal banking sector is avoided for these transactions 6. Bhagwati et al (2017) also view 30% as the eventual equilibrium laundering fee.…”
mentioning
confidence: 99%